ISSUES TO IMPROVE THE COST OF PRODUCTION OF ENVIRONMENTALLY CLEAN PRODUCTS - Avlaev Muzaffar Tuflievich (Journals Park Publishing, 2022)
The article explores the concept of environmental quality in detail. The need to research the theory and methodology of accounting for environmental quality costs of products is scientifically based. The opinions of economists regarding the category of quality have been studied. Also, the importance of considering quality as an ecological category is highlighted. A description of the concept of ecological quality is presented. Based on the analysis of economic literature and the study of practice, an author's approach to the environmental quality of the product was developed. Six main aspects of ecological quality: social, technical, legal, economic, aesthetic and ecological aspects are studied in detail. The composition of environmental quality costs and accounting objects have been determined based on the directions for improving the environmental quality of products.
Keywords: quality, social aspect, Environmental Quality